RANCANG BANGUN APLIKASI SISTEM PAKAR UNTUK MENDIAGNOSA KERUSAKAN PRINTER BARCODE MENGGUNAKAN METODE FORWARD CHAINING - Mega Wahyu Rhamadani; Dedi Setiawan (Fakultas Teknik Unkris Jakarta, 2023)
Damage to a printer, especially a barcode printer, often annoys users, in general, users bring the barcode printer to the printer service. The length of time the barcode printer is repaired at the service point can also take up time. In addition to the costs that will be incurred to repair the device as well as possible opportunities that lead to fraud at the service site. The ability of a technician to detect printer damage can be implemented into an application system. An application system that can work as a human or an expert works is known as an expert system. Forward Chaining is a fact to get a conclusion from that fact.This reasoning is based on available facts (data driven). The forward-chaining algorithm is also one of the two main methods of reasoning when using an inference engine and can logically be described as a looping application of the modus ponens (a set of inference rules and valid arguments).